IMPLEMENTASI METODE KARIMAH DALAM PEMBELAJARAN MEMBACA AL-QUR’AN DI PUSAT PENDIDIKAN AL-QUR’AN (PPQ) AL MAHIR, COLOMADU, KARANGANYAR - Desti Widiani Widiani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
The ability of the tilawah of the majority of Muslims is still weak. It is seen that there are still frequent mistakes in khaffi and jalli when reading the holy verses of the Qur'an while giving speeches, preaching or when becoming priests in congregational prayers. Many factors cause this situation, and especially the most important factor is the method of teaching that lacks manhaji. In general, the methods in learning the Qur'an today cannot provide an alternative solution for beginner learners to learn to read the Qur'an easily, practically, systematically, and in accordance with the rules of recitation. Karimah as one of the methods of reading the Qur'an which is applied in the Al-Qur'an Education Center Al Mahir Colomadu Karanganyar is one of the alternative methods to help beginners who want to read the Qur'an easily, practically, systematically, and in accordance with the rules of recitation. The purpose of this study was to determine the implementation of the Karimah method in Al-Qur'an learning at the Al-Qur'an Education Center (PPQ) Al Mahir Colomadu Karanganyar. The results of this study are the implementation of Al-Qur'an reading at the Al-Mahir Colomadu Karanganyar Al-Qur'an Education Center (PPQ) easy, practical, systematic, and in accordance with the rules of recitation. The implementation of the Karimah method begins with the opening, the cult, the teaching of reading the Qur'an and closing. Teaching Al Qu'an reading with the Karimah method is divided into 3 stages namely beginner, pre-tahsin and tahsin.